First Case of CD40LG Deficiency in Ecuador, Diagnosed after Whole Exome Sequencing in a Patient with Severe Cutaneous Histoplasmosis - Pedroza, Luis Alberto; Guerrero, Nina; Stray-Pedersen, Asbjørg; Tafur, Cristina; Macias, Roque; Muñoz, Greta; Akdemir, Zeynep Coban; Jhangiani, Shalini N.; Watkin, Levi B.; Chinn, Ivan K.; Lupski, James R.; Orange, Jordan S. (Frontiers in Pediatrics, 2017)
Severe infections with Histoplasma capsulatum are commonly observed in patient with secondary immunodeficiency disorders. We presented a two and a half years old boy previously healthy, with disseminated cutaneous Histoplasmosis. Using Whole Exome Sequencing we found an indel mutation at the CD40LG gene, suggesting a diagnosis of Hyper IgM Syndrome, even in the absence of the usual features for the disease. Interestingly the patient lives in a region endemic for Histoplasmosis. The unusual infections in our case suggest that in children with severe histoplasmosis and resident in endemic areas, Hyper IgM Syndrome should be considered as a diagnosis.